FATWA HARAM GOLPUT DALAM PERSPEKTIF SOSIOLOGI HUKUM ISLAM - Ahmad 'Ubaydi Hasbillah (Program Studi Hukum Keluarga Islam, 2015)
In the current democratic system in Indonesia, the discourse on abstentions rises exceeding the number of votes in the general election. Religion has contributed to the succession in Indonesia since the end of representative democracy. The Council of Indonesian Ulama has released fatwa on the prohibition of abstention. To what extent does the fatwa correspond to situation in Indonesia? How is MUI legal reasoning to prohibit abstention? How was the fatwa born? How was public response to the fatwa? Through the perspective of sociology of Islamic law, this paper tries to reconstruct the position of fatwa in front of Qur’an and Hadith prescriptions on unlawful leadership.